2011
DOI: 10.4103/0019-5049.84861
|View full text |Cite
|
Sign up to set email alerts
|

Immediate postoperative extubation after liver transplantation at our centre: A report of two cases

Abstract: Liver transplantation is a dynamic field undergoing continuous changes in management. Prolonged postoperative mechanical ventilation has been a norm but now there is a trend towards early extubation. We developed a protocol for early extubation based on bispectral index monitoring. This protocol was applied in two cases with satisfactory outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Hence, experience with only a few cases of FT LDLT recipients has been published so far. [ 11 12 ] The small proportion of FT recipients in our high-volume centre confirms this difficulty with LDLT recipients.…”
Section: Discussionmentioning
confidence: 64%
“…Hence, experience with only a few cases of FT LDLT recipients has been published so far. [ 11 12 ] The small proportion of FT recipients in our high-volume centre confirms this difficulty with LDLT recipients.…”
Section: Discussionmentioning
confidence: 64%
“…In the 1980s, early endotracheal extubation in the operating room (E-OR) was first applied in cardiac surgery, and later in liver transplantation (8,9). E-OR can decrease the costs and the complications associated with mechanical ventilation such as hemodynamic instability, pulmonary colonization of gastrointestinal micro-organisms, sepsis, risks of barotrauma, and bronchial anastomosis leaks caused by the need for sedatives or opioids to inhibit gastrointestinal motility (10).…”
Section: Original Articlementioning
confidence: 99%
“…Studies have shown that postoperative pulmonary rehabilitation can improve the activity endurance of patients after lung transplantation, improve lung function, and effectively r e d u c e p o s t o p e r a t i v e c o m p l i c a t i o n s ( 7 , 8 ). E a r l y endotracheal extubation is firstly used in 1980s in cardiac and liver surgery (9). Early endotracheal could reduce the cost and ventilation associated complications (10).…”
Section: Introductionmentioning
confidence: 99%